Case studies : applying educational psychology - Jackson, Dinah L.; Ormrod, Jeanne Ellis (Upper Saddle River, N.J. : Merrill, 1998)
Illustrates principles related to learning (cognitive psychology, constructivism, social cognitive theory, and behaviorism), motivation (attribution theory, intrinsic motivation), child development (Piaget, Vygotsky, Kohlberg), diversity (cultural and gender differences), and students with special needs (physical disabilities, learning disabilities, mental retardation, emotional disturbance, and traumatic brain injury)
Keywords: School psychology -- United States -- Case studies; Educational psychology -- Case studies